PEMBELAJARAN ILMU TAJWID PENGARUHNYA TERHADAP KEMAMPUAN MEMBACA AL QURAN - Hadian, Dhandy Bhima Shakty; Safwandy, Mulyawan; Nursobah, Asep; Al Bahal, Manal (Jurnal Al Burhan, 2024)
This study aims to analyze the influence of Tajweed learning on the ability to read the Quran among 8th-grade students at Al Karimah Islamic Junior High School in Bogor. The research method used is qualitative, involving 22 students as research subjects. Three chapters of the Quran, namely Al-Bayyinah, Al-Zalzalah, and Al-‘Adiyat, were used as test objects to evaluate reading ability, articulation points (Makharijul Huruf), and tajweed knowledge. The results showed that most students could read the three chapters well, with 16 students for Al-Bayyinah, 19 students for Al-Zalzalah, and 20 students for Al-‘Adiyat. In the aspect of articulation points, most students demonstrated good ability, with 18 students for Al-Bayyinah, 17 students for Al-Zalzalah, and 21 students for Al-‘Adiyat. Meanwhile, in tajweed knowledge, the results showed that the majority of students could answer tajweed questions well, with 18 students for Al-Bayyinah, 19 students for Al-Zalzalah, and 19 students for Al-‘Adiyat. Thus, tajweed learning has a positive impact on the Quran reading ability of 8th-grade students at Al Karimah Islamic Junior High School, showing significant improvement in the tested aspects.